A review of domestic waste management policy and law in Singapore. Issue 1 (September 2021) - Syme, Rosie
Abstract : An effective waste management system is, and has always been, essential infrastructure, particularly given the potential for waste to adversely impact the surrounding environment. In recent decades, however, there has been growing awareness of the scale, breadth and immediacy of those adverse impacts, and of the unsustainability of the enormous (and increasing) amount of waste society generates. Governments around the world have mobilised and there has been a widespread shift towards policies promoting circular economies, waste minimisation and maximised resource efficiency. Singapore is a case in point; despite having a traditionally high waste output and a waste management system dependent on waste incineration as the primary means of disposal, Singapore has committed to a zero waste future. This article presents a review of domestic waste management policy and law in Singapore. Several gaps in the legal framework are identified and considered against the broader context, leading to the conclusion that there is a material environmental vulnerability in the legal framework that should be redressed in order to entrench environmental protections and to align the law with Singapore's policy ambitions. Notwithstanding this deficiency, it is hard not to be optimistic about the future of domestic waste management in Singapore, as the government has made an ambitious policy commitment and appears to be pursuing it with vigour.